Fundamental motor skills in chilean preschoolers - Fernández-Valero, Paz Belén (2022)
Fundamental Motor Skills (FMS) have been identified as a key factor in fostering active, healthy lifestyles throughout life. However, FMS findings among preschoolers are mixed. The objective of this study is to describe the categorization of the scores obtained in the FMS test, as well as to clarify the differences by sex and age. A cross-cutting design study was carried out with 145 preschool children (84 of them boys) of ages 4 to 6 (5.44 ± 0.58 years old) participating in a national program of the Ministry of Sports. FMS were measured by using the gross motor development test (second edition). For the category analysis of the FMS, the scores obtained in the test were converted to percentiles, presented through frequency tables. In order to analyze sex and age differences, U of Mann-Whitney and Kruskal-Wallis were used for those without normal distribution, and the Student t and one-way ANOVA analyses for variables with normal distribution. The main outcomes indicate that preschoolers mostly obtain scores above the ≥p50 percentile. Boys showed higher ≥p50 scores in locomotion skills, object control (p = 007) and total FMS than girls. Boys and girls showed higher ≥p50 scores with increase in age in locomotion skills (p = .002), object control (p <.001) and total FMS (p <.001). In conclusion, Chilean preschoolers show fair performance in FMS, and manifest significant differences by sex and age, mainly in object control.